12 Myths and Facts about Physical Education for Students with Disabilities. Issue 1 (2nd January 2020) - Bittner, Melissa; Silliman-French, Lisa; Lieberman, Lauren J.; Lytle, Rebecca
Abstract : According to the Individuals with Disabilities Education Act every student that has a documented disability is required to have an individualized education program (IEP). The IEP comprises core areas, including physical education. The purpose of this article is to clarify 12 myths about physical education for students with disabilities and help general physical education and classroom teachers. Lastly, this article will provide suggestions for teachers to get involved in the IEP process and be a valuable member of the team to ensure a high quality of physical education for all students.